SOCIAL MARKETING-MIX ELEMENTS AND DRUG ABUSE DEMARKETING IN NIGERIAN UNIVERSITIES - Odigbo, Ben E. Ph.D, Aniebiet, Etuk, Ph.D, Akpam, Victor Ategwu (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study examined the effect of social marketing-mix elements on youths’ drug abuse in public universities in Cross River State, Nigeria. The research was sparked by the observation that marketing programs aimed at reducing the menace of drug abuse amongst university students have not been fully implemented in the State. Data were collected from volunteered 397 students of the University of Calabar and Cross River State University of Technology, Nigeria, through random sampling technique, using a four-point likert scale questionnaire, and analyzed with Principal Component Analysis (PCA). The results revealed that the social marketing-mix elements (product, price, place, promotion, publics and policy) examined significantly influenced demarketing of drug abuse in public universities in Cross River State, Nigeria. Hence, it was recommended that social marketers,should design and package their campaigns to target audiences on the ills of drug abuse in universities and colleges, toreflect social marketing-mix elements, so that the target audience do not feel embarrassed, criticized, withdrawn or engage in denials; and programmes aimed at demarketing drug abuse should be affordable and accessible to the target audience.